"Habermasville": Police–Community Intersections and Communicative Rationality. Issue 4 (1st October 2020) - McCandless, Sean; Vogler, G. M.
Abstract : Police–community relations in the United States are seeing a crisis of trust and legitimacy. Minorities disproportionally experience police contact, and recent shootings of unarmed persons raise concerns about whether minority communities have equal protection of the law. This paper uses Jürgen Habermas's theory of communicative rationality to examine this distrust. The argument is that Habermas's theory positively informs understanding of police–community relations in that distrust is caused by lack of communicative acts in favor of strategic acts emphasizing crime control that maintains unjust systems.